Dopamine reuptake site densities in patients with social phobia - TIIHONEN, J; KUIKKA, J; BERGSTRÖM, K; LEPOLA, U; KOPONEN, H; LEINONEN, E (The American journal of psychiatry, 1997)
OBJECTIVE: It has been suggested that social phobia is associated with dysfunction of the noradrenergic and dopaminergic systems, but there are no published anatomic data on the monoaminergic abnormalities found in the brains of phobic patients. The authors studied the density of dopamine reuptake sites in patients with social phobia. METHOD: The study included 11 patients with social phobia and 28 healthy comparison subjects, 11 of whom were age- and gender-matched to the patients for the analyses. Measurement of the density of dopamine reuptake sites was performed by using a 123I-labeled cocaine analogue, [123I]beta-CIT, with single photon emission computed tomography (SPECT). RESULTS: Blind quantitative analysis revealed that striatal dopamine reuptake site densities were markedly lower in the patients with social phobia than in the age- and gender-matched comparison subjects. CONCLUSIONS: The results indicate that social phobia may be associated with a dysfunction of the striatal dopaminergic system.